Solution for suppressing viscoelastic creep in cylindrical dielectric elastomer actuator - Nguyen, Tuan Dung; Tran, Anh Vang (Journal of Military Science and Technology, 2025)
The cylindrical dielectric elastomer actuator (CDEA) is known as a self-prestretching structure of dielectric elastomer actuators (DEAs). However, their inherent viscoelastic nonlinearity leads to nonlinear viscoelastic creep and hysteresis, which makes the modeling and control of CDEAs challenging and can affect their motion accuracy in practical applications. In this paper, the generalized KV-GM rheological model is employed to characterize the actuator’s viscoelastic creep behavior, and an adjusted voltage signal is derived from maintaining a constant output stretch by making the input voltage time-dependent. Experimental results with the preprogrammed voltage demonstrate that the creep rate of the CDEA decreases from 27% to less than 9%. The proposed solution effectively minimizes energy dissipation caused by nonlinear viscoelastic properties, playing a significant role in promoting the practical application of CDEA.